Cardiorenal Syndrome: A Physician Perspective - Deepak Jain; HK Aggarwal; Promil Jain; Pulkit Chhabra (Archives of Clinical Nephrology - Peertechz Publications, 2017)
Cardiac diseases are associated independently with decrease in kidney function and progression of existing kidney diseases. Conversely, chronic kidney disease (CKD) represents an independent risk factor for cardiovascular events and outcomes. Renal dysfunction frequently accompanies cardiac failure and that cardiac dysfunction frequently accompanies renal failure. This interdependent relationship has come to be known as the "cardiorenal syndrome". Direct and indirect effects of each organ that is dysfunctional can initiate and perpetuate the combined disorder of the two organs through a complex combination of neurohormonal feedback mechanisms. In this review pathophysiology and management of fi ve different subtypes of cardiorenal syndrome is discussed.